Geochemical Characteristic of the Carbonaceous Sediments of the Upper Paleozoic Kuantan Group, Malaysia - Burgan, Amer M (Journal of Applied Geology, 2024)
The geochemical parameters discussed in this paper are based on an average values of twelve outcrop carbonaceous samples, mainly black shales, were determined using X-Ray Fluorescence (XRF) and Inductively Coupled Plasma-Mass Spectrometer (ICP-MS) techniques, representative of Charu, Sagor, and Permian formations.The aim of this study is to define and discuss their characteristics, the distribution abundance of major and minor elements, investigation the dominant mineralogical composition and reconstruct the depositional environment for these sediments.The bulk chemical result showed that, the average values of the major elements are 65.83%, 64.82 %, 71.4 % SiO2, 18.27 %, 22.2 %, 15.66 % Al2O3, 1.53 %, 0.99 %, 2.49 % Fe2O3. 4.06 %, 6.25 %, 3.66 %  K2O , whereas in the case of the miner elements, the results read values of 524.4 ppm, 758.8 ppm, 446.3 ppm Ba , 366 ppm, 399.3 ppm, 257.3 ppm Rb, 88 ppm, 67.3 ppm, 47.3 ppm Sr , 308 ppm, 288.8 ppm, 327ppm Zr for the Charu, Sagor, and Permian  formations  respectively. The major oxides reflect the dominant mineralogical composition of quartz and other silicate minerals (e.g. illite, kaolinte, smectite) and deficiency in carbonates.The high Rb/K ratio suggests brackish marine environment or rapid depositions that prevent equilibrium between Rb and K in these study shales and marine environment. The high Rb/Sr ratios of 4.16, 5.89 and 5.44 for the Charu, Sagor, and Permian formations respectively possibly attributed to the lowest contents of Sr content due to reducing environment prevailing during deposition of these sediments.